Philosophy of the Uzbek National Martial Arts (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
V dannoy state rassmatrivayutsya uzbek vostochnye edinoborstva, ix razvitie i ix philosophiskie vzglyady. Uzbek Eastern martial arts play an important role in the physical, mental, emotional and aesthetic education of a person. V state otmechaetsya znachenie vostochnyx uzbekskikh edinoborstv v vospitanii vsestoronne razvitoy lichnosti.